Masonry buildings at the borderline to high‐rise – Part 2 / Mauerwerksbauten an der Hochhausgrenze – Teil 2: Verification of bracing systems with stress fields / Nachweis von Aussteifungssystemen mit Spannungsfeldern. Issue 3 (June 2016) - Seim, Werner; Sommerlade, Kai
Abstract: For the verification of framing shear walls of masonry, the decisive combination of actions derives from the interaction of vertical and horizontal actions. In this article, a method based on simple truss models is extended for the transfer of horizontal actions. It is demonstrated how the required verifications of load‐bearing safety can be performed with the results of the structural calculation. As an example, the application of the method for a seven‐storey building with calcium silicate blockwork or Poroton brick masonry is described.